The Regulation of Traditional Villages as Legal Subjects and the Designation of Temples as Religious Legal Entities in Relation to Land Ownership Rights - Anak Agung Sagung Laksmi Dewi; I Nyoman Sumardika; I Gusti Agung Ayu Gita Pritayanti Dinar; I Made Minggu Widyantara; Anak Agung Ngurah Adhi Wibisana (Fakultas Hukum, Universitas Warmadewa, 2024)
This study aims to discuss the implementation of the Bali Provincial Regulation which has given birth to various legal provisions regarding the registration of land rights, both for Customary Village and Temple land, both of which are recognized as legal entities. The material is presented using a normative approach to identify legal rules and principles. The legal sources for this study are derived from statutory provisions, including: 1) Law No. 5 of 1960 on the Basic Agrarian Law (UUPA), 2) Government Regulation No. 24 of 1997, 3) Bali Provincial Regulation No. 4 of 2019 on Customary Villages, 4) Ministerial Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 276/KEP-19.2/X/2017 on the Designation of Customary Villages in Bali Province as Legal Subjects for Joint (Communal) Land Ownership, 5) Minister of Home Affairs Decree No. 556/DJA/1986 on Legal Entities Eligible for Land Ownership Rights. The results of the study show that the Traditional Village was officially designated as the subject of customary rights based on the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 276/KEP-19.2/X/2017 concerning the Determination of Traditional Villages in Bali Province as Subjects of Collective (General) Land Ownership Rights. Procedurally, the initial land ownership certification process for Pura followed the standard land certification procedure. It began with a written application submitted to the Head of the National Land Agency Office of Tabanan Regency, accompanied by the required administrative documents.